Production of high temperature grease from waste lubricant sludge and silicone oil - Yeung, Cheryl Suet Ling (2010)
This research was carried out to study the production of high temperature grease from waste lubricant sludge and silicone oil. The effects of different ratios of waste lubricant sludge to fumed silica and mixing time on grease characteristics were investigated. The ratios of waste lubricant sludge and fumed silica used were 100:0, 90:10, 80:20, 70:30, 60:40, 50:50 and 40:60. In terms of mixing time, it was varied at 1, 2, 3, 4 and 5 hours. Throughout the experiment, the grease was prepared by using the heating and mixing technique. The grease produced was analysed according to the ASTM and NLGI standard via penetration test, dropping point test, copper corrosion test, FTIR and AAS.Fourier transform infra red (FTIR) analysis was carried out to study on the functional groups present in the grease. Atomic absorption spectroscopy analysis was also carried out to determine the concentration of a specific metal element in the grease. The results showed that the grease produced with a minimum ratio of fumed silica to sludge (10:90) was able to produce high temperature grease with a dropping point of 272.5.C.Further analysis verified that the grease is a high temperature grease, has worked penetration of 270-290 which makes the grease fall into the common grease category, has a low tendency to corrode copper and very little metal element was present in the grease. It can be concluded that the ratio of fumed silica to sludge and the mixing time of the grease produced significant effect on worked penetration and dropping point of the grease.